In-situ CO2 generation for EOR by using urea as a gas generation agent. (1st April 2018) - Wang, Shuoshi; Chen, Changlong; Shiau, Benjamin; Harwell, Jeffrey H.
Highlights: The effectiveness of applying urea as a gas generating agent in in-situ CO2 EOR is proved. Urea shows better divalent cations tolerance than previously studied gas generating agent (ammonium carbamate). In-situ CO2 Generation EOR has better performance with lighter crude oil. Operating above the MMP is not a necessary criterion for achieving high tertiary recovery of in-situ CO2 EOR. Oil composition change in the recovered oil was detected before and after tertiary recovery. Abstract: While injection of CO2 has great potential for increasing oil production, this potential is limited by site conditions and operational constraints such as lack of proper infrastructure, limited cheap CO2 sources, viscous fingering, gravity override at the targeted zones, and so forth. To mitigate some of these common limitations, we explore alternative methodologies which can successfully deliver CO2 through gas generation in situ, with superior IOR performance, while offering reasonable chemical cost. A new approach of in situ CO2 generation EOR was proved through a series of high-pressure and high-temperature laboratory scale experiments in this work. Urea was selected as a potential source of generating CO2 in situ because of its remarkable availability at bulk quantity and resistance to divalent cations. Urea is highly soluble in fresh water or brine and can decompose at reservoir conditions spontaneously to release carbon dioxide and ammonia. The tertiary oil recovery performance of the urea solution was evaluated in sand pack flooding at different operational conditions. We studied the flow rate ranging from 13.6 in./day to 36.2 in./day, the urea concentration ranging from 5% to 35%, the pressure ranging from 1500 psi to 4000 psi and the oil API ranging from 27 to 57.3, either with or without the presence of divalent ions. Recovered oil compositional analyses also revealed the additional benefits from the produced ammonia in tertiary recovery. Most importantly, results of injecting urea solution (as low as 5% solution) showed superior tertiary recovery performance (as high as 37.5%) as compared to the most recent efforts at our group (29.5%) as well as similar in situ CO2 generation EOR (2.4%–18.8%) approaches proposed by others. Because of the remarkable reservoir brine compatibility of urea, even under seawater levels of divalent ions, the floods showed no detectible effect of brine composition on the recovery and/or any occurrence of formation damage. Furthermore, the preferable wettability reversal was indicated by recovered oil compositional analyses. The economic feasibility and advantages of the newly proposed technique were demonstrated. The results served as a proof of concept for in situ CO2 generation tertiary oil recovery potential for both onshore and offshore fields.